Mobilizing youth in crime prevention program: a case of Malaysia - Abdul Mutalib, Rozita; Arshad, Rozita; Ahmad, Zalinah; Mohd Othman, Fazilah (2017)
Reducing Crime is one of the efforts that had been outlined in the Government Transformation Program (GTP) by the Malaysia Government. Various policies and efforts had been implemented to minimize crime rate and subsequently improve the quality of life of the citizens. Many programs and policies as counter measures of crime involving youth were also done. Nonetheless, it does not really address the whole problem. For instance, the government introduced the Reducing Crime National Key Results Area (nKR4) to combat crime, as well as upgraded public security and the per$ormance of the Royal Malaysian Police ( P D W . The rate of crimes committed by youths has increased although the overall crime index in the country has decreased Hence, concerted actions not only by all enforcement and related government machineries are necessary but more significantly the initiative and involvement of all Malaysians are required. Since youth constitutes around 45 percent of the Malaysia total population, their participation in combating crime in community is very crucial. Therefore, this paper tried to explore crime issues and situation involving youth in Malaysia and how to mobilize them in all of the strategies and programs outlined in the country.